EXPLORING SECONDARY SCHOOL STUDENTS’ COGNITIVE STRUCTURES OF ENVIRONMENTAL POLLUTION AND THE FOOD CHAIN: AN ECOLOGICAL AND EDUCATIONAL PERSPECTIVE - Zeynep Yüce; Gamze Bulut (MOJES: Malaysian Online Journal of Educational Sciences, 2025)
Environmental components, including soil, water, air, and biodiversity, are vital for maintaining the balance of the ecosystem. However, environmental pollution is one of the most significant threats to these balances. With environmental pollution, the balance of ecosystems is disrupted, and the food chain is negatively affected. The food chain, which establishes equilibrium among plants, animals, and microorganisms, is of critical importance for the consumption of healthy food by humans. Understanding these relationships is crucial for grasping the cause-and-effect relationships underlying environmental issues. Consequently, the concepts of environmental pollution and the food chain are interconnected, and comprehending this relationship through education is necessary to cultivate more environmentally conscious generations. This study aims to determine the conceptual knowledge levels of 8th-grade students regarding the concepts of environmental pollution and food chain, as well as to reveal the conceptual schemas present in their cognitive structures. During the 2022-2023 academic year, the study was conducted with 286 eighth-grade students enrolled in schools within a district located in the eastern region of Türkiye. The research was conducted as a qualitative study using a survey model. The Word Association Test (WAT) was employed as the data collection instrument. The findings indicate that students established connections between "Environmental Pollution" and "Food Chain" but failed to fully grasp the relationships among these concepts and their interrelated effects. The results suggest that the cognitive relationships between environmental pollution and the food chain need to be emphasized more explicitly.